Experimental models in interventional neuroradiology. - TerBrugge, K G; Lasjaunias, P; Hallacq, P (American Journal of Neuroradiology, 1991)
Various experimental models have been developed to test interventional neuroradiologic techniques. Most have been used to test various devices and embolic materials, and a small number of models have been designed for teaching or training purposes. Experimental models in endovascular techniques have seldom been used to stimulate disease processes in order to facilitate their understanding.